Autonomic Neuropathy in Obesity - Akhter, Shahin; Begum, Noorzahan; Ferdousi, Sultana; Khan, MD Sakhawat Mahmud (Journal of Bangladesh Society of Physiologist, 2011)
Background: Obesity is one of the health problems and the association of autonomic nerve dysfunction with certain cardiovascular disorders may exist in obese subjects. Objective: To observe the status of autonomic nerve function activity in order to detect the presence of autonomic neuropathy in obese persons. Methods: This study was conducted in Physiology department of Bangabandhu Sheikh Mujib Medical University during July 2006-June 2007. 40 apparently healthy obese subjects of both sexes with BMI >25 were included. Age and sex matched 40 nonobese subjects with BMI range 18.5- 22.9 were also included for comparison(control). 5 noninvasive cardiovascular reflexes tests were done and scoring of autonomic neuropathy was also detected. Unpaired Student ‘t’ test was used for statistical analysis. Results: Mean values of all cardiovascular reflex tests were significantly lower in obese subjects. Autonomic neuropathy in its early involvement stage was found in 22.5% of the obese subjects. Conclusion: The results of this study indicate that autonomic neuropathy though in early stage may be silently present in otherwise healthy obese person. DOI: http://dx.doi.org10.3329/jbsp.v6i1.8059 J Bangladesh Soc Physiol. 2011 June; 6(1): 5-9